Penambahan Menu Web Survei di Website Badan Perencanaan Pembangunan Daerah dan Penelitian Pengembangan Kota Samarinda - Arif Nur Rahman; Ibnu Sabdaniansyah; Muhammad Rifqi Pratama; Wawan Joko Pranoto (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The Regional Development Planning Agency and Research and Development of Samarinda City are striving to enhance the quality of services and community participation in the planning and development processes. One proactive measure taken is the integration of a web survey menu into the institution's official website with the title "Preparation of the Initial Draft of Samarinda City's RPJPD for the Years 2025-2045." This research aims to add a web survey menu to support efficiency, effectiveness, and interactivity in community data collection. The method utilized for creating this website is the data collection method. The results obtained from this community service initiative include the successful development of a website implemented at the Regional Development Planning Agency and Research and Development of Samarinda City, eliminating the need for manual data input.